Recent Publications Books and Pamphlets (Quarterly Journal of Economics, 1936)
Recent Publications Books and Pamphlets Get access The Quarterly Journal of Economics, Volume 50, Issue 3, May 1936, Pages 540–544, https://doi.org/10.1093/qje/50.3.540 Published: 01 May 1936